2015
DOI: 10.1177/0741932515572911
|View full text |Cite
|
Sign up to set email alerts
|

Students With Disabilities and Involvement in Peer Victimization

Abstract: Bullying can have destructive consequences for our young people. And it's not something we have to accept. As parents and students; teachers and communities, we can take steps that will help prevent bullying and create a climate in our schools in which all of our children can feel safe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 91 publications
1
24
0
1
Order By: Relevance
“…Children with disabilities are at a higher risk to be victims of bullying than students without disabilities [38,39,40,41,42,43,44,45,46,47,48,49,50]. Rose et al [51] reported that two of the most important predictors of being bullied for students with disabilities were a lack of social skills and a lack of communication skills.…”
Section: Introductionmentioning
confidence: 99%
“…Children with disabilities are at a higher risk to be victims of bullying than students without disabilities [38,39,40,41,42,43,44,45,46,47,48,49,50]. Rose et al [51] reported that two of the most important predictors of being bullied for students with disabilities were a lack of social skills and a lack of communication skills.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, researchers (T. Farmer et al, 2015;Rose, Monda-Amaya, & Espelage, 2011) have suggested that there is a paucity of literature focused on bullying and SWD. Previously, researchers (T. Farmer et al, 2015;Rose, Monda-Amaya, & Espelage, 2011) have suggested that there is a paucity of literature focused on bullying and SWD.…”
Section: Resultsmentioning
confidence: 99%
“…Several authors (e.g., T. Farmer, Wike, Alexander, Rodkin, & Mehtaji, 2015;O'Brennan, Waasdorp, Pas, & Bradshaw, 2015) have suggested that students with more externalizing behaviors are at increased risk for being bully-victims while students with more obvious intellectual or physical disabilities are more prone to victimization. Several authors (e.g., T. Farmer, Wike, Alexander, Rodkin, & Mehtaji, 2015;O'Brennan, Waasdorp, Pas, & Bradshaw, 2015) have suggested that students with more externalizing behaviors are at increased risk for being bully-victims while students with more obvious intellectual or physical disabilities are more prone to victimization.…”
Section: Bullying and Swdmentioning
confidence: 99%
“…This does not concern all students with disabilities, but more often those with physical disorders or disorders of autistic spectrum (Lindsay, & McPherson, 2012). They are limited in contacts with classmates after classes and are not integrated into peer activities in class (Farmer, Wike, Alexander, Rodkin, & Mehtaji, 2015).…”
Section: Problem Statementmentioning
confidence: 99%